Emotional Intelligence and Academic Self-Efficacy in Relation to the Psychological Well-Being of University Students During COVID-19 in Venezuela - García-Álvarez, Diego; Hernández-Lalinde, Juan; Cobo-Rendón, Rubia (Frontiers in Psychology, 2021)
Due to the COVID-19 pandemic, educational centers and universities in Venezuela have closed their physical plants and are migrating to emergency remote education to continue with academic programs. This empirical study aimed to analyze the predictive capacity of academic self-efficacy and emotional intelligence skills on each of the dimensions of psychological well-being. We employed a cross-sectional predictive design. The sample comprised 277 university students, of which 252 were female (91.00%). Their ages ranged from 18 to 45 years, with a mean of 20.35 (SD=2.29). Non-probabilistic chance sampling was used. For data collection, we used an anonymous online form, contacted students by mail, and invited them to participate in the study. Questionnaires were available between 217 and 227 days of decreed quarantine in Venezuela. The results indicated average levels of academic self-efficacy (Me=4; IQR=2), emotional intelligence: clarity (Me=27; IQR=10), attention (Me=25; IQR=10) y repair (Me=25; IQR=12), and psychological well-being (Me=35; IQR=5). We found differences according to sex and age, specifically in emotional regulation (z=3.73, p<.001, d= 0.438) and in bonds of psychological well-being (z=2.51, p=.012, d= 0.276) favoring men (Me=33, IQR=9; Me=8, IQR=1), respectively. Regarding age, statistically significant differences were found in the group of students older than 21 years with higher perception of psychological well-being (z=3.69, p<.001, d=0.43) and in each of its dimensions. Emotional intelligence and academic self-efficacy were found to be significant predictors of psychological well-being and its dimensions, specifically on control (R2-Cox=.25, R2-Nagelkerke=.34, 69.90% of total correct classification), links (R2-Cox=.09, R2-Nagelkerke=.12, 65.07% of total correct classification), projects (R2-Cox=.32, R2-Nagelkerke=.46, 78.40% of total correct classification), acceptance (R2-Cox = .17, R2-Nagelkerke = .23, 68.28% of total correct classification) and total well-being (R2-Cox=.52, R2-Nagelkerke =.71, 87.16% of total correct classification). It was concluded that emotional intelligence and academic self-efficacy are protective psychological resources of psychological well-being that should be promoted at university to mitigate the negative effects of the pandemic on the mental health of young people.